The Court of Arbitration for Sport - An assessment of its structure and jurisdiction - Brüggemann, Falko (Department of Commercial Law, 2019)
The dissertation examines the system and history of arbitration in sport, assessing its benefits, problems and potential. It reveals and considers the special features of sports and the consequential needs for the way of dispute settlement in this area. For this purpose, at first a brief overview about the concept of arbitration in general is given, followed by an objective description of the history and structure of the Court of Arbitration for Sport as the most important dispute settlement body in sports. By reference to these ascertained developments regarding its composition and operation, the quality of the Court of Arbitration for Sport will be evaluated and its common criticism will be analysed in detail. Moreover, in this context, the necessity of state control for sports arbitration will be revealed, making specific reference to a main case study of Claudia Pechstein vs. the International Skating Union which will help to illustrate the manifestations of the acquired problems and their context in practice. The case study thereby also reveals the different approaches of the various courts that dealt with the case and hence serves to reflect on their assessments. For these reasons, the case of Claudia Pechstein will be studied in detail, starting with the background of the case and illuminating all the judicial proceedings from the Court of Arbitration for Sport up to the Federal Supreme Court of Germany. The thesis then examines whether the found results also apply from South African perspective and hence can be transferred to South African law as well. Finally, it attempts an outlook in respect of the future of arbitration in international sports. To this effect, the dissertation tries to provide solutions for the problems of the Court of Arbitration for Sport by considering the interests of all involved parties and thereby lend credence to the respective arbitral judgements.